2016 New talent: crystal engineering at its biggest and strongest. Issue 22 (23rd May 2016) - Banerjee, Rahul; Day, Graeme M.; Friščić, Tomislav; Zhang, Hongjie
Abstract : Welcome to the 2016 New talent issue of CrystEngComm.